2021
DOI: 10.1073/pnas.2101492118
|View full text |Cite
|
Sign up to set email alerts
|

Auxin guides germ-cell specification in Arabidopsis anthers

Abstract: Germ cells (GCs) are the key carriers delivering genetic information from one generation to the next. In a majority of animals, GCs segregate from somatic cells during embryogenesis by forming germlines. In land plants, GCs segregate from somatic cells during postembryonic development. In a majority of angiosperms, male GCs (archesporial cells) initiate at the four corners of the anther primordia. Little is known about the mechanism underlying this initiation. Here, we discovered that the dynamic auxin distrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…After incubation, the samples were washed two or three times in 10 mM phosphate buffer and 0.1% (vol.vol −1 ) BSA for 10 min at a time and then washed with 10 mM phosphate-buffered saline (PBS) and 0.8% (wt.vol −1 ) BSA for 10 min. Anti-rabbit secondary antibody Fluor 488 was diluted in 1:500 blocking solution, incubated for 4 h at room temperature, protected from light, washed twice with 10 mM PBS, 0.88% (wt.vol −1 ) NaCl, 0.1% (vol.vol −1 ) Tween 20, and 0.8% (wt/vol −1 ) BSA for 15 min each time, and then washed for 1 min with 10 mM PBS and blocked with glycerol ( Zheng et al, 2021 ). After Zeiss fluorescence microscopy imaging (Axio Imager D2), final editing was performed using Photoshop 2019.…”
Section: Methodsmentioning
confidence: 99%
“…After incubation, the samples were washed two or three times in 10 mM phosphate buffer and 0.1% (vol.vol −1 ) BSA for 10 min at a time and then washed with 10 mM phosphate-buffered saline (PBS) and 0.8% (wt.vol −1 ) BSA for 10 min. Anti-rabbit secondary antibody Fluor 488 was diluted in 1:500 blocking solution, incubated for 4 h at room temperature, protected from light, washed twice with 10 mM PBS, 0.88% (wt.vol −1 ) NaCl, 0.1% (vol.vol −1 ) Tween 20, and 0.8% (wt/vol −1 ) BSA for 15 min each time, and then washed for 1 min with 10 mM PBS and blocked with glycerol ( Zheng et al, 2021 ). After Zeiss fluorescence microscopy imaging (Axio Imager D2), final editing was performed using Photoshop 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Tapetum differentiation is regulated by many genes in rice [17,18]. Notably, mutants with aberrant MMC differentiation also fail to differentiate the tapetum properly, similar to that found in Arabidopsis [19][20][21][22]. It has therefore been suggested that tapetum differentiation is dependent on MMC differentiation [17,23].…”
Section: Introductionmentioning
confidence: 75%
“…SPL/NZZ was suggested to be involved in auxin homeostasis 49 . A recent study showed that auxin distribution is associated with differentiation of the male germ cell PMC (pollen mother cell) 50 . Mutations in auxin biosynthesis genes TAA1 ( TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS 1 ) and TAR2 ( TRYPTOPHAN AMINOTRANSFERASE RELATED 2 ) impair the PMC formation, whereas ectopic expression of SPL / NZZ partially rescues the PMC specification.…”
Section: Discussionmentioning
confidence: 99%